Developing an assessment tool for geropsychiatric mental healthcare knowledge and attitude evaluations in clinical practice for nursing students - Chia‐Shan Wu; Mei‐Fang Chen; Jiin‐Ru Rong; Chieh‐Yu Liu (Wiley, 2021)
Abstract Aim To develop an instrument to investigate geropsychiatric psychological symptoms, health problem nursing knowledge (GPN‐K), geropsychiatric psychological symptoms and health problem nursing attitude scale (GPN‐A) in clinical practice for nursing students. Design Instrument development and cross‐sectional study for psychometric testing. Methods Construct validity was evaluated using confirmatory factor analysis (CFA) and exploratory factor analysis (EFA), and internal consistency was calculated using Cronbach's α. Results A total of 300 students have completed the questionnaires (85.71% response rate). The CFA of GPN‐K showed good fitness and validity. The Kuder‐Richardson 20 (KR‐20) value of the internal consistency reliability is 0.64. The GPN‐A overall content validity index is 0.95. A three‐factor structure was shown by exploratory factor analysis. The three factors are communication and care, helping others improve and problem evaluation tendency. The total variance explained is 59.01%. Cronbach's alpha of GPN‐A equals 0.84, which represents good internal consistency.